2022
DOI: 10.1021/acs.langmuir.2c00813
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Polymer Contact Electrification: Modeling the Dependence of Surface Charges and ξ-Potential on pH and Added-Salt Concentration

Abstract: Here, a mathematical model is presented, which accounts for the dependence of the surface electrical charge density (σ) on pH and the concentration of added salts (C s), generated when a water drop rolls or slides on the surface of a hydrophobic polymer, a process known as liquid–polymer contact electrification (LPCE). The same model was successfully applied to fit the isotherms of ξ-potential as a function of pH, reported in the literature by other authors for water–poly­(tetrafluoroethylene) (PTFE) interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(64 citation statements)
references
References 58 publications
7
55
2
Order By: Relevance
“…This is in contrast to a solution of HCl (green squares), which for the smallest concentrations does not alter the charge transfer to within the experimental uncertainty, but beyond 5 μM gives rise to a strong decrease. Moreover, it is found that for HCl concentrations in the range 0.1–1 mM, the charge transfer changes sign and becomes negative, as was also reported in refs and . This reversal of charge transfer can also be seen from the green curve in Figure a.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…This is in contrast to a solution of HCl (green squares), which for the smallest concentrations does not alter the charge transfer to within the experimental uncertainty, but beyond 5 μM gives rise to a strong decrease. Moreover, it is found that for HCl concentrations in the range 0.1–1 mM, the charge transfer changes sign and becomes negative, as was also reported in refs and . This reversal of charge transfer can also be seen from the green curve in Figure a.…”
Section: Methodssupporting
confidence: 86%
“…It also explains the observed increase in charge transfer for increasing pH up to 10, as well as the decrease in charge transfer with salt concentration. However, the theory presented in ref does not naturally explain why dissolved salts give rise to the same increase in charge transfer for small concentrations as is observed in Figure . In the current work, it is shown that by some modifications of the theory of ref , clarifying the various contributions to charge transfer, one may construct a chemical equilibrium theory which explains all the features mentioned earlier.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations